KIAA1549: BRAF Gene Fusion and FGFR1 Hotspot Mutations Are Prognostic Factors in Pilocytic Astrocytomas. Issue 7 (July 2015) - Becker, Aline Paixão; Scapulatempo-Neto, Cristovam; Carloni, Adriana C.; Paulino, Alessandra; Sheren, Jamie; Aisner, Dara L.; Musselwhite, Evelyn; Clara, Carlos; Machado, Hélio R.; Oliveira, Ricardo S.; Neder, Luciano; Varella-Garcia, Marileila; et al.
Abstract : Abstract: Up to 20% of patients with pilocytic astrocytoma (PA) experience a poor outcome. BRAF alterations and Fibroblast growth factor receptor 1 ( FGFR1 ) point mutations are key molecular alterations in Pas, but their clinical implications are not established. We aimed to determine the frequency and prognostic role of these alterations in a cohort of 69 patients with PAs. We assessed KIAA1549:BRAF fusion by fluorescence in situ hybridization and BRAF (exon 15) mutations by capillary sequencing. In addition, FGFR1 expression was analyzed using immunohistochemistry, and this was compared with gene amplification and hotspot mutations (exons 12 and 14) assessed by fluorescence in situ hybridization and capillary sequencing. KIAA1549:BRAF fusion was identified in almost 60% of cases. Two tumors harbored mutated BRAF . Despite high FGFR1 expression overall, no cases had FGFR1 amplifications. Three cases harbored a FGFR1 p.K656E point mutation. No correlation was observed between BRAF and FGFR1 alterations. The cases were predominantly pediatric (87%), and no statistical differences were observed in molecular alterations–related patient ages. In summary, we confirmed the high frequency of KIAA1549:BRAF fusion in PAs and its association with a better outcome. Oncogenic mutations of FGFR1, although rare, occurred in a subset of patients with worse outcome. These molecular alterations may constitute alternative targets for novel clinical approaches, when radical surgical resection is unachievable.